EFFECT OF BIOCHAR RESIDUE, COMPOST, AND UREA COMBINATION ON GROWTH AND YIELD OF MAIZE (ZEA MAYS L.) - MOHD. CHALISZAR; . ZAITUN; E. NURAHMI (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2014)
The objective of this study was to know the effect of biochar residue, compost and urea fertilization on growth and yield of maize.  The research was conducted at University Farm Ie Seum Research Station, Aceh Besar district, Aceh Province, Indonesia.  The experimental arranged in a randomized complate block non factorial design with four replications.  There were eight treatment combinations: P1 (without biochar residue + without compost + without urea), P2 (without biochar residue + without compost + urea), P3 (without biochar residue + compost + without urea), P4 (without biochar residue + compost + urea), P5 (biochar residue + without compost + without urea), P6 (biochar residue + without compost + urea), P7 (biochar residue + compost + without urea), P8 (biochar residue + compost + urea).  Based on the plant growth, biochar residue, compost, and urea fertilizer treatment did not significantly affect on plant height age of 30, 45 and 60 days after planting, leaf number aged 30, 45 and 60 days after planting, stem diameter ages 30, 45 and 60 days after planting. At the P7 treatment (biochar residue + compost + without urea) gave the best value but does not differ significantly with all treatments tested.  Based on plant yield, biochar residue, compost, and urea fertilizer treatment did not significantly affect on cornhusk ear length, cornhusk cob diameter, cornhusk cob weight, cob length without cornhusk, cob diameter without cornhusk, cob weight without cornhusk, and yield.  At P5 treatment (biochar residue + without compost + without urea) cornhusk cobs and P7 (biochar residue + compost + without urea) cornhusk cobs and without cornhusk provide the best value but does not differ significantly with all treatments tested.